Caso radiológico: Fratura do tipo torus - Macedo, F (2013)
We present a case of a six-year old child with wrist pain after sustaining trauma the previous day. The x-ray revealed a torus fracture of the distal radio metaphysis. The torus fracture is one of the fractures occurring in the immature skeleton. Some specific types of children fractures are described as well as the value of the imaging techniques for the diagnosis.